2009
DOI: 10.1007/s13149-009-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

État actuel de la toxoplasmose dans la région de Sfax, Tunisie

Abstract: The frequency of toxoplasmosis depends on life-style and environment. Our objective was to study different epidemiological, clinical and biological aspects of toxoplasmosis in the Sfax area (Tunisia). This retrospective study has been performed on seria of 40,566 pregnant women in the Parasitology-Mycology Laboratory of Habib-Bourguiba Sfax hospital-Tunisia for 13 years from 1994 to 2006; 1,691 patients presenting with lymphadenopathy; 191 immunocompromised patients (78 HIV infected patients and 113 transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Our overall seroprevalence finding is consistent with that found in Tunis, North Tunisia, (47.7%) in a cross-sectional study including all pregnant women who presented for serological testing of toxoplasmosis [11]. A retrospective study in the Sfax region, East Tunisia, showed that the seroprevalence rate of pregnant women was 46.1% during the years 1994-1997, 41.3% from 1998 to 2001, and 36.9% from 2002 to 2006 [34]. An earlier study showed that the seroprevalence in the general population from Tunisia was 45.9% [3].…”
Section: Discussionsupporting
confidence: 89%
“…Our overall seroprevalence finding is consistent with that found in Tunis, North Tunisia, (47.7%) in a cross-sectional study including all pregnant women who presented for serological testing of toxoplasmosis [11]. A retrospective study in the Sfax region, East Tunisia, showed that the seroprevalence rate of pregnant women was 46.1% during the years 1994-1997, 41.3% from 1998 to 2001, and 36.9% from 2002 to 2006 [34]. An earlier study showed that the seroprevalence in the general population from Tunisia was 45.9% [3].…”
Section: Discussionsupporting
confidence: 89%
“…Other surveys focused on pregnant women and congenital toxoplasmosis [19,25,114]. The seroprevalence rates range from 39.3% in the southern regions to 47.7% in the northern regions using ELISA [26,56,111]. Most of the Tunisian authors suspected consumption of undercooked meat and unwashed vegetables as the two main contamination routes [56].…”
Section: Toxoplasma Gondii Infection In Algeriamentioning
confidence: 99%
“…Toxoplasmosis is regularly diagnosed in immunocompromized patients in Tunisia. Before highly active antiretroviral therapy (HAART), cerebral toxoplasmosis was reported as one of the most prevalent infections in patients with HIV [111].…”
Section: Toxoplasma Gondii Infection In Algeriamentioning
confidence: 99%
“…One case, after duplicate, was removed, and 36 cases were excluded according to exclusion criteria i (out of scope) and iv (insufficient available data). In the present review we only analyzed cases regarding SOT recipients published from 1996 to 2016 and available on the PubMed database with sufficient data for inclusion on synthesis of results (n 907) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , ...…”
Section: Resultsmentioning
confidence: 99%
“…In published and available reviewed literature, we found 162 case reports of toxoplasmosis occurring after SOT [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Of interest, in SOT recipients, toxoplasmosis results more frequently from transmission of the parasite with the transplanted organ from a Toxoplasma -seropositive donor (D+) to a Toxoplasma -seronegative recipient (R−).…”
Section: Discussionmentioning
confidence: 99%